Consumers knowledge regarding pesticides on apples and effective washing to remove the pesticides - Brar, Arvinder; BCIT School of Health Sciences, Environmental Health; Sidhu, Bobby (BCIT Environmental Public Health Journal, 2015)
Objectives: With the increased health awareness, there is a growing demand of fresh produce in food. Not only is there a possibility of the fresh produce to be contaminated with harmful micro-organisms, but also chemicals such as pesticides that have harmful adverse effects. The effective method of washing the fruit can reduce the level of pesticide residue to a significant amount. The objective of the study is to determine if the general public is aware of washing the produce properly and if knowledge, age, gender, education or concerns have any association with the effectiveness of washing. Methods: The study was done using a survey that was designed using Google Forms. An online survey which was self-administered was sent out using snowball sampling. The survey was publicized through both email and social media Facebook. The survey had 19 questions in total 11 of which were general and 8 were knowledge based. The results were analysed by Chi-square test using NCSS Software Package. Results: It was found that there is a statistically significant association between knowledge level and effective method of washing the apples with a p-value of 0.00082. This means H0 is rejected; hence it means there is an associative between knowledge level and effectively washing the apples. No other demographic factors (age, gender, education, concerns, or having children) were found to be associated with the method of washing the produce effectively. Conclusion: It was found through the study that the people who were aware and had good knowledge about the presence of chemicals (pesticides) on apples would wash their fruit (apples) effectively enough that will reduce the pesticide residue on fruits more than people who aren’t aware of the pesticides on fruits. Other factors such as age, gender, preference for the type of food were not found to have any association with washing of the fruit effectively or higher level of knowledge.